Моніторинг і оцінка розвитку особистісного потенціалу підлітків у скаутських громадських об‘єднаннях - Сапіга, Світлана; Sapiha, S. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлюється важливість розвитку особистісного потенціалу підлітків у скаутських громадських об’єднаннях, підкреслюючи, що підлітковий вік є важливою фазою в загальному процесі становлення людини як особистості. Розглядаючи розвиток особистісного потенціалу підлітків, автор наголошує на ролі громадських скаутських об’єднань в організації цього процесу. Він акцентує увагу на необхідності здійснення моніторингу і оцінки розвитку особистісного потенціалу підлітків та розглядає механізми та алгоритми його проведення у скаутських громадських об’єднаннях. Автор виділяє умови для проведення моніторингу та оцінки розвитку особистісного потенціалу підлітків та пропонує критерії та показники, якi є своєрідними індикаторами прояву певної якості та характеризують ступінь розвитку того чи іншого компоненту особистісного потенціалу підлітків в скаутських громадських об’єднаннях. The article highlights the importance of developing the personal potential of adolescents in Scout NGOs, emphasizing that adolescence is an important phase in the overall process of becoming a person as an individual. Considering the development of the personal potential of adolescents, the author notes the role of public scout associations in the organization of this process. It emphasizes the need for monitoring and evaluation of personal potential of adolescents and consider mechanisms and algorithms of its holding in the scouting community associations. The author provides conditions for monitoring and evaluation of the development of personal potential of adolescents and proposes criteria and indicators that are original indicators of manifestation of a certain quality and characterize the degree of development of the physical, spiritual, emotional, volitional, social, intellectual components of the personal potential of adolescents in Scout public associations. Among these - time, which is necessary for communication with adolescents, establishing contacts with family, teachers, the immediate environment of a teenager; balanced approach, attentiveness and dedication of an adult leader; a certain number of adolescents is observed, followed by a specific adult leader; a clearly defined observation period; taking into account the assessment of other subjects in the educational process: parents, teachers, adult leaders, volunteers who take part in the activity of the Scout Association; taking into account peer opinions; taking into account the results of self-esteem of a teenager.
Monitoring and evaluation of the development of the personal potential of adolescents in Scout public associations
Keywords: розвиток особистісного потенціалу підлітків; скаутські громадські об’єднання; моніторинг і оцінка; спостереження та самооцінка; development of personal potential of adolescents; scout public associations; monitoring and evaluation; observation and self-evaluation